Engineering mechanics - Meriam, J. L. (John Wiley, 1998)
Statics,contains 75 sample problems and 960 unsolved problems from which a wide choice of assignments can be made. Of these problems, more than 50 percent are new to the fourth Edition. SI units are used throughout the book.